The rise in cash holdings of Danish companies - Simone Maria Bonin; Tobias Renkin (Danmarks Nationalbank, 2022)
The distribution of cash holdings across Danish companies has changed dramatically since the onset of the Global Financial Crisis, with the median company more than doubling its cash reserves in the last ten years. Cash holdings are highly heterogeneous across companies. Large companies, less profitable companies, companies with less risky cash flows and companies in the manufacturing sector tend to hold smaller cash reserves. While structural changes in the Danish economy cannot explain the development of cash holdings, we find that increased cash holdings covary strongly with a simultaneous decrease in loan financing. Changes in the distribution of loan debt can explain most of the increase in cash holdings. The increase in cash holdings and loan financing is driven by entry and exit patterns: after 2007, companies with low cash holdings are more likely to exit, while entering companies have higher cash reserves. Overall, our results are consistent with companies reacting to more difficult access to credit by increasing their precautionary cash buffers.
Keywords: 330; Cash-Management; Kredit; Unternehmensfinanzierung; Betriebliche Finanzwirtschaft; Dänemark